Seroprevalence and determinants of Echinococcus granulosus sensu lato infection among owned dogs in Ibadan, Nigeria - Adebudo, Lucky Icomiare; Ndiaye, Sirin; Ajayi, Ikeoluwapo; Olugasa, Babasola Oluseyi; Bonelli, Piero; Awosanya, Emmanuel Jolaoluwa (The Journal of Infection in Developing Countries, 2023)
Introduction: Humans acquire cystic echinococcosis through accidental ingestion of Echinococcus granulosus (EG) eggs released into the environment by infected dogs. This study aimed to determine the presence of EG antibodies and their determinants in owned dogs in Ibadan, Nigeria. Methodology: Sera from 185 dogs on routine visits to veterinary clinics were analysed by indirect ELISA. A questionnaire was administered to dog owners to obtain data on demographics, management, and environmental factors. Data were analysed using descriptive statistics, univariate analysis, and logistic regression at α0.05. Results: The median age of the dogs was 20 months (range 2 – 96). The seroprevalence of EG infection was 33.51% (95% CI: 26.71, 40.32%). Low educational level of dog owners (OR: 2.8; 95% CI: 1.3, 5.8); local dog breeds (OR: 3.2; 95% CI: 1.7, 6.0); confinement (OR: 0.4; 95% CI: 0.2, 0.8); interaction with other dogs (OR: 3.2; 95% CI: 1.4, 7.3); self-dewormed dogs (OR: 2.6; 95% CI: 1.2, 5.9) and never dewormed dogs (OR: 4.39; CI: 1.9, 10.0) were significantly associated with EG seropositivity. Our results suggest also that local breed of dog (AOR: 2.4; 95% CI: 1.2, 4.9), self-deworming of dogs (AOR: 2.6; 95% CI: 1.1, 5.9) and the absence of any dog deworming treatment (AOR: 2.9; 95% CI: 1.2, 7.1) might be predictive of EG seropositivity. Conclusions: Our study provides evidence of EG infection in owned dogs, especially in those medicated by owners. Deworming practices should be based on the recommendations of a veterinarian to effectively prevent EG transmission from dogs to humans.